Endoscopic Balloon Dilation for Crohn's Disease-Associated Strictures - Thomas Klag; Jan Wehkamp; Martin Goetz (Korean Society of Gastrointestinal Endoscopy, 2017)
Management of intestinal strictures associated with Crohn's disease (CD) is clinically challenging despite advanced medical therapy directed toward mucosal healing to positively influence the natural course of CD-associated complications. Although medical therapy is available for inflammatory strictures, therapy of fibrostenotic strictures is the domain of surgery and endoscopy. Endoscopic balloon dilation (EBD) has been recognized as a well-established first-line procedure in terms of safety and efficacy. Although surgery is a valuable treatment modality for the management of CD-related strictures, EBD can help prevent multiple surgical interventions, which might in the long-term lead to a risk of short bowel syndrome. In this review we discuss requirements, techniques, safety, short- and long-term outcomes, as well as combinations of this procedure with surgical and medical treatment in CD-associated intestinal strictures.